Identifikasi Sidik Jari Dalam Mengungkap Tindak Pidana Pencurian - Andi Rumpang; Muhammad Sabir Rahman; Muhammad Natsir (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2021)
The fingerprint is one of the technologies that can be used to identify a person. Even today, the fingerprint is a technology that is considered quite reliable because it is proven to be relatively accurate, safe, and comfortable to use as identification when compared to other biometric systems. This study aims to determine the legal strength of fingerprint-proof in the process of investigating a criminal act of theft based on the Criminal Procedure Code. This research uses empirical normative research with a statute approach. The results showed that. The fingerprint-proof system does not require witnesses, because, in terms of proof of fingerprint identification, the minimum provisions for proving the two pieces of evidence should be fulfilled by the existence of a certificate regarding the fingerprint, documentary evidence plus a statement from a dactyloscopy expert as one of the legal evidence. One of the obstacles faced by investigators when they are at the crime scene to collect/find evidence of fingerprints is if the place of the incident has changed its authenticity or is contaminated. Efforts are made by investigators to work around this by seeking the police or investigating officers to immediately be alert and responsive in receiving public reports about the existence of a crime.